Animal nutrition - Lambourne, L.J.; Dicko, M.S.; Semenye, P.P.; Butterworth, M.H. (International Livestock Centre for Africa, 1983)
Discusses the effects of the interaction among genotype, animal health & nutrition on livestock productivity within a particular environment, w. spec. ref. to results of work undertaken by ILCA on the nutrition component of the system, using availability & composition of forage, and composition & amount of food eaten to study grazing behaviour, feed intake and performance of animals.